#### Answer

z = $\frac{3}{4}$

#### Work Step by Step

$\frac{3(2 - z)}{5}$ = z
Multiply both sides by 5:
3(2 - z) = 5z
Distribute:
6 - 3z = 5z
Add 3z to both sides:
6 = 8z
Divide both sides by 8:
$\frac{6}{8}$ = z
$\frac{3}{4}$ = z

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

z = $\frac{3}{4}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.